2005
DOI: 10.1051/0004-6361:20042352
|View full text |Cite
|
Sign up to set email alerts
|

Star counts in the Galaxy

Abstract: Abstract. We describe TRILEGAL, a new populations synthesis code for simulating the stellar photometry of any Galaxy field. The code attempts to improve upon several technical aspects of star count models, by: dealing with very complete input libraries of evolutionary tracks; using a stellar spectral library to simulate the photometry in virtually any broad-band system; being very versatile allowing easy changes in the input libraries and in the description of all of its ingredients -like the star formation ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
753
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 663 publications
(777 citation statements)
references
References 61 publications
21
753
0
1
Order By: Relevance
“…Such stars are also likely to overlap with other parts of the CMD, notably the RGB, which can lead to confused interpretation of the stellar populations. However, the number and CMD distribution of putative foreground sources appear wellmatched to models of distribution of MW stars (e.g., Girardi et al 2005;de Jong et al 2010), allowing for straightforward accounting of intervening sources.…”
Section: The Cmd and Membership Identificationmentioning
confidence: 99%
“…Such stars are also likely to overlap with other parts of the CMD, notably the RGB, which can lead to confused interpretation of the stellar populations. However, the number and CMD distribution of putative foreground sources appear wellmatched to models of distribution of MW stars (e.g., Girardi et al 2005;de Jong et al 2010), allowing for straightforward accounting of intervening sources.…”
Section: The Cmd and Membership Identificationmentioning
confidence: 99%
“…The selection region for BHB and BS stars are shown with the blue and red polygons, respectively. We use the Trilegal Galaxy model (Girardi et al 2005) to estimate the foreground contamination included in our A-type star samples. The estimated foreground in the BHB and BS CMD selection regions is subtracted before the BS-to-BHB fractions are computed.…”
Section: Dwarf Galaxiesmentioning
confidence: 99%
“…We integrated the flux in the CMD subtracting the flux contribution from foreground MW halo giants and metal-poor MW dwarfs and from background galaxies. In order to estimate and remove the contamination, we used the predictions from the TRILEGAL Galaxy model (Girardi et al 2005) scaling the number of predicted MW stars to the number observed in our fields in those parts of the CMDs that were clearly devoid of MB InterCloud stars (see Gallart et al 2004 andNoël & for more details). The upper y-axis shows redshift for our current cosmology.…”
Section: Surface Brightness Profilesmentioning
confidence: 99%